Diseño y construcción de una máquina semiautomática para la fabricación de bloques vibro-prensados de 15 centímetros con capacidad de cuatro unidades por minuto para la Empresa Mayorga Ponce - Guatemal Granada, Edith Fernanda (2017)
Design and construction of semiautomatic machine for 15 centimeters vibropressed blocks, capacity of four units per minute for Mayorga Ponce Factory has the purpose of the present document. The way to make concrete blocks usually is a simple deficient process. To obtain the product don´t apply national building regulations such as NTE INEN 643, this project endeavors to satisfy needs with high quality products, meeting customer demands. Chapter five is divided in the document, as follows: All issues of general concepts of building, concrete blocks, fabrication process, and kinds of machines available in the market such as manual, semiautomatic, automatic are contained in the first chapter. Second chapter shows different ways to design the semiautomatic machine for 15 centimeters vibropressed blocks, capacity of four units per minute, comparing feasibility, maintenance, and viability. Finally choose the most suitable model through an analysis of advantages and disadvantages. Graphics of simulation, material selection, and machine parts calculation are performed in the third chapter, each under the specifications of Ecuador`s current technical standards for the manufacture of concrete blocks such as NTE INEN 638 and NTE INEN 643. In the fourth chapter, the manufacturing cost analysis, the net present value (NPV) and internal rate return (IRR) appears, during the semiautomatic machine for 15 centimeters vibropressed blocks, capacity of four units per minute construction. Finally the conclusion and recommendation of this work are presented in the fifth chapter.